1996
DOI: 10.1016/0014-5793(96)00071-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel 28‐kDa secretory protein from rat olfactory epithelium

Abstract: We have isolated a novel secretory 28-kDa protein which is an abundant component of the rat olfactory mucosa. The partial sequence of the 28-kDa protein has been determined. The amino acid sequence of the 28-kDa protein is similar to that of non-selenium glutathione peroxidase from bovine ciliary body. The 28-kDa protein catalyzed decomposition of the hydrogen peroxide as well as organic hydroperoxides by reduced glutathion and seems to be a member of the glutathion peroxidases family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 12 publications
1
27
0
4
Order By: Relevance
“…Thus, C48 and H441 cells had similar potential to respond to a cytokine-induced stress and the relative resistance of C48 cells seems to be specific for the oxidant-mediated membrane lipid peroxidation pathway. Discussion 1-CysPrx is a recently described member of the peroxiredoxin family that is expressed at relatively high levels in the lungs, eyes, and olfactory epithelium (3,9,20,21). Overexpression of the protein in 3T3 cells has been shown to increase the ability of these cells to degrade H 2 O 2 and protects them against H 2 O 2 -mediated inactivation of glutamine synthetase (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, C48 and H441 cells had similar potential to respond to a cytokine-induced stress and the relative resistance of C48 cells seems to be specific for the oxidant-mediated membrane lipid peroxidation pathway. Discussion 1-CysPrx is a recently described member of the peroxiredoxin family that is expressed at relatively high levels in the lungs, eyes, and olfactory epithelium (3,9,20,21). Overexpression of the protein in 3T3 cells has been shown to increase the ability of these cells to degrade H 2 O 2 and protects them against H 2 O 2 -mediated inactivation of glutamine synthetase (6).…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies indicated that GSH could function as a reductant with 1-cysPrx isolated from bovine eye (20) or rat olfactory epithelium (21), although the latter result subsequently could not be reproduced (22). Studies with recombinant protein also have been inconclusive because GSH has been effective in some studies (7,23) but not in others (6).…”
Section: Resultsmentioning
confidence: 99%
“…The 2-cysPrx, also referred to as thioredoxin peroxidases, reduce peroxides with electrons provided by thioredoxin (28,29). 1-cysPrx, also named Prx VI, is capable of reducing peroxides in the presence of small thiols such as dithiothreitol (1, 2, 7) or glutathione (2,3,4,6). We have recently demonstrated that depletion of glutathione diminishes activity of the enzyme in intact cells, indicating that it can serve as a physiological electron donor (23).…”
Section: Discussionmentioning
confidence: 99%
“…1-cysPrx, also named peroxiredoxin VI, is a member of this superfamily that can reduce phospholipid hydroperoxides (PLOOH) as well as organic peroxides and H 2 O 2 (1-3). 1-cysPrx has been isolated from bovine ciliary epithelium (4,5), rat olfactory epithelium (6,7), and rat and bovine lungs (8,9); Northern and immunoblot analyses of mammalian tissues show the presence of 1-cysPrx in all organs with especially high levels of 1-cysPrx protein and mRNA expression in lung (8,10). 1-cysPrx is a bifunctional enzyme with both glutathione peroxidase (GPx) and phospholipase A 2 (PLA 2 ) activities (3).…”
mentioning
confidence: 99%
“…In plants, antioxidant activity has been demonstrated for the 2-Cys BAS1 (Baier and Dietz, 1997) and the 1-Cys PER1 (Stacy et al, 1996) of barley (Hordeum vulgare). Transgenic plants overexpressing the rice (Oryza sativa) 1-Cys Prx (R1C-Prx) exhibit higher resistance to oxidative stress, suggesting antioxidant activity (Lee et al, 2000) in accordance with the function of 1-Cys homologs in other organisms (Shichi and Demar, 1990;Netto and Stadtman, 1996;Peshenko et al, 1996).…”
mentioning
confidence: 99%